2022
DOI: 10.3389/fpls.2022.892676
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution dissection of photosystem II electron transport reveals differential response to water deficit and heat stress in isolation and combination in pearl millet [Pennisetum glaucum (L.) R. Br.]

Abstract: Heat and Water Deficit Stress (WDS) tend to impede and restrict the efficiency of photosynthesis, chlorophyll fluorescence, and maximum photochemical quantum yield in plants based on their characteristic ability to interfere with the electron transport system in photosystem II. Dissection of the electron transport pathway in Photosystem II (PSII) under water deficit and Heat Stress (HS) can be insightful in gaining knowledge on the various attributes of the photosynthetic performance of a plant. We attempt a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…When we look at the ability to regulate leaf temperature, we find that in general all lines manage to adjust the temperature below the ambient temperature (negative values of LTD). This mechanism is possibly triggered by the higher loss of water at the leaf surface allowing to keep the leaf surface cooler, managing to maintain an optimal metabolism [76], and as mentioned by Shanker et al [77] a decrease in the vapor pressure deficit within the leaf. It is possible that heat stressed plants are trying to minimize the irreversible damage that can be caused by the combined stress.…”
Section: Capacity Of Photosynthetic Apparatus For Coping With Soil Ac...mentioning
confidence: 94%
See 1 more Smart Citation
“…When we look at the ability to regulate leaf temperature, we find that in general all lines manage to adjust the temperature below the ambient temperature (negative values of LTD). This mechanism is possibly triggered by the higher loss of water at the leaf surface allowing to keep the leaf surface cooler, managing to maintain an optimal metabolism [76], and as mentioned by Shanker et al [77] a decrease in the vapor pressure deficit within the leaf. It is possible that heat stressed plants are trying to minimize the irreversible damage that can be caused by the combined stress.…”
Section: Capacity Of Photosynthetic Apparatus For Coping With Soil Ac...mentioning
confidence: 94%
“…The identification of these mechanisms is important because: 1) photosynthesis is the process that contributes most to CB production; 2) an adequate mechanism in energy dissipation is related to a better translocation of assimilates (PHI and HI for pod and grain formation); 3) variations in electron transport due to heat stress can be reflected in the yield obtained also [77,[87][88][89][90]. Based on the results of this study, we found that nine biofortified common bean lines [F5: 859, 805, 865, 657, 653; F4: 2853, 2796, 2815, 3730], have traits with potential for adaptation to the combined stress of acid soils and high temperatures.…”
Section: Differences In Physiological Response Between Common Bean Li...mentioning
confidence: 99%
“…When we look at the ability to regulate leaf temperature, we find that in general, all lines manage to adjust the temperature below the ambient temperature (negative values of LTD). This mechanism is possibly triggered by the higher loss of water at the leaf surface, allowing the leaf surface to be cooler, managing to maintain an optimal metabolism [73], and, as mentioned by Shanker et al [74], a decrease in the vapor pressure deficit within the leaf. It is possible that heat-stressed plants are trying to minimize the irreversible damage that can be caused by the combined stress.…”
Section: Capacity Of Photosynthetic Apparatus For Coping With Soil Ac...mentioning
confidence: 96%
“…Br.] ( Shanker et al., 2022 ). The damage to the oxygen evolution complex (OEC) was predominant in heat-stressed, but not in drought-stressed plants.…”
Section: D/+h Stress-induced Physiological and Molecular Responses In...mentioning
confidence: 99%
“…The damage to the oxygen evolution complex (OEC) was predominant in heat-stressed, but not in drought-stressed plants. Additionally, OEC damage-induced low exciton absorption flux was evident in HS and H+D stress, causing electron transport congestion in the donor side of PSII ( Shanker et al., 2022 ). These results showed that combined D+H stress was more dominant than the individual stresses on the overall electron transport pathway of the PSII ( Shanker et al., 2022 ).…”
Section: D/+h Stress-induced Physiological and Molecular Responses In...mentioning
confidence: 99%